Rewriting Pain: Trauma, Memory, and Healing in Frankie Riley’s All the Dark Places (Sastra Inggris UNPAM, 2026)
This study examines the representation of trauma in Frankie Riley’s All the Dark Places (2022) by analyzing how traumatic experiences are articulated through intrinsic poetic elements. Using a qualitative descriptive approach, the research focuses on selected poems that portray themes of anxiety, abandonment, emotional abuse, and healing. The analysis is grounded in Cathy Caruth’s trauma theory (1996), particularly her concepts of repetition, belatedness, and the fragmented nature of traumatic memory. The findings reveal that trauma in Riley’s poetry is depicted not as a single past event but as a recurring psychological condition that continuously shapes identity and emotional experience. Through recurring metaphors such as drowning, storms, cages, and scars, the poems transform abstract suffering into vivid sensory imagery. Repetition of phrases such as “Some days,” “And so, I became,” and “I’m learning” reflects the cyclical return of painful memories while also signaling gradual personal growth. These patterns align with trauma theory, which emphasizes the intrusive and repetitive character of traumatic experience. The study further demonstrates that intrinsic elements—including diction, imagery, structure, tone, and figurative language—function as central mechanisms for expressing trauma. Riley’s simple yet emotionally charged diction conveys immediacy and vulnerability, while fragmented structures mirror psychological instability. Shifts in tone from despair to empowerment illustrate a movement toward self-awareness and resilience. Figurative language, particularly metaphor and parallelism, enables the articulation of experiences that are otherwise difficult to express directly.